Using internet in improving students' writing skill / Suria Azhani Ali - Ali, Suria Azhani (2012)
This paper is a research the use of integrating the internet for year five and six pupils. The study is to investigate the effectiveness of using internet in improving pupils writing skills. It is hope that the pupils will enjoy and interested in language learning especially in writing skill. The research conducted by using experiment in two groups of pupils. They are experimental and controlled groups. The experimental group was given treatment but the control group used conventional method of teaching during this research. The research instruments used in this research are observation, questionnaires, interviews and tests. The qualitative research was done in order to analyze the data through out interpretations of questionnaires, interviews and observations.